Development and effectiveness of digital classroom assessment document for form one mathematics in secondary school - Nasir, Nurihan; Adnan, Mazlini; Rajoo, Murugan; Ismail, Anis Oweeda; Hidayat, Riyan (Modestum, 2024)
Classroom assessment is essential for tracking students’ progress and improving teaching and learning in the classroom. However, the lack of clear documentation to guide teachers in assessing student mastery often hinders effective communication between teachers and stakeholders about the students’ progress. This study aimed to develop and test the digital classroom assessment document (CA-Do) for form one mathematics to improve classroom assessment practices. Design research and development method, based on ADDIE model, was used to create the digital CA-Do, and 55 mathematics teachers from 55 schools were sampled using stratified sampling. The data collected was then analyzed using SPSS version 27. The digital CA-Do received a satisfactory expert validity score of content validity index (1.00), and found all four tested sub-constructs (i.e., usefulness, ease of use, ease of learning, and satisfaction of use) to be of high level. There were significant differences in teachers’ knowledge post-familiarization with the digital CA-Do. The study concludes that the digital CA-Do can aid teachers in recording the intervention and impact of teaching and learning information and consistently assessing pupils’ mastery level. This research provides guidance to educators on how to modify their classroom assessment strategies to enhance teaching outcomes and classroom assessment methods, particularly formative assessment.